Inbreeding in Al-Jabal Al-Akhdar, Libya: Evidence from the Fixation Index and Heterozygosity of Blood Groups - Aljebali, Ahmad; Sulaiman , Nisreen; Mansur , Ahmad (AlQalam Journal of Medical and Applied Sciences, 2026)
This study investigates levels of inbreeding among several towns in the Al-Jabal Al-Akhdar region of Libya using the ABO blood group system as a genetic marker. Analyses focused on observed heterozygosity (HO), expected heterozygosity (HE), and the fixation index (FIS), an estimate of the inbreeding coefficient. The Chi-Square Goodness-of-Fit Test was used to compare the proportions of the FIS across different towns. Results showed a large variation in genetic diversity across towns. The HO ranged from 0.380 to 0.550, with Derna, Maraweh, and Shahat showing the highest diversity. In contrast, Al-Bayadah, Al-Haniya, Al-Qubah, and Qandula displayed high positive FIS values, indicating an excess of homozygotes and suggesting high inbreeding within these local populations. However, there is no statistically significant difference in the FIS of ABO blood types across towns in Al‑Jabal Al‑Akhdar. These findings highlight the need for further genetic and demographic studies to understand the factors that contribute to population inbreeding and substructure.